Intention to breastfeed during Covid-19 pandemic and its associated factors - Mazlan, Nurul Atikah Natasha; Abd Rahman, Mohd Aizuddin; Muhd Helmi, Muhd Alwi; Hasan, Taufiq Hidayat (Universiti Putra Malaysia, 2024)
Introduction: The COVID-19 pandemic affects breastfeeding practise in numerous ways. Various factors could affect the intention of women to breastfeed. This study aims to assess the intention to breastfeed during the COVID-19 pandemic and its associated factors. Methods: A cross-sectional study was conducted using online, self-administered, validated questionnaires on 291 Malaysian women. Respondents were International Islamic University Malaysia Kuantan staff and visitors who gave birth between June 2021 and June 2022, identified through a convenient sampling method. The questionnaire consisted of 17 items on intentions to breastfeed during the pandemic, each with three Likert-scale response options. The prevalence of respondents with high and low intention to breastfeed was calculated. Mean scores between respondents with different sociodemographic backgrounds were compared using a one-way ANOVA or t test. Results: The prevalence of the participants who have high intentions to breastfeed during COVID-19 pandemic was 73%. Maternal education level, income group, previous breastfeeding experiences, mother’s occupation, the jaundice status of the baby and mother’s knowledge were significantly associated with high intention to breastfeed during the COVID-19 pandemic. Conclusion: During the COVID-19 pandemic, the intention to breastfeed remained high. In order to empower breastfeeding practises, stakeholders should take the initiative to provide appropriate breastfeeding education and a supportive environment to the community.